2008
DOI: 10.1007/s10995-008-0381-x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Gestational Weight Gain and Diet on Abnormal Glucose Tolerance During Pregnancy in Hispanic Women

Abstract: Objective To examine the association of gestational weight gain and dietary factors with abnormal glucose tolerance (AGT). Methods We conducted a prospective cohort study among 813 Hispanic prenatal care patients in Massachusetts. Gestational weight gain and oral glucose tolerance test results were abstracted from medical records. Dietary intake was assessed using a semi-quantitative food frequency questionnaire. Target weight gain was based on BMI-specific weekly weight gain rates established by the Institu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 61 publications
(61 reference statements)
3
38
1
Order By: Relevance
“…However, we found a clear association between excessive GWG and the risk of GDM. Our analysis does not provide evidence of effect modification by maternal BMI category, which has been suggested previously [15,37]. However, stratified data to assess this were only reported in four studies [17,22,33,34].…”
Section: Discussioncontrasting
confidence: 51%
“…However, we found a clear association between excessive GWG and the risk of GDM. Our analysis does not provide evidence of effect modification by maternal BMI category, which has been suggested previously [15,37]. However, stratified data to assess this were only reported in four studies [17,22,33,34].…”
Section: Discussioncontrasting
confidence: 51%
“…In the gestational period, the literature focuses on and reports the existence of predisposition to diabetes in obese women (25,35) rather than the independence of the prepregnancy BMI category. Also, in recent years, a relationship has been found between excessive weight gain according to the Institute of Medicine BMI classification for weight gain recommendations and glucose intolerance without actually resulting in the pathology (19).…”
Section: Discussionmentioning
confidence: 99%
“…A more recent cohort study also revealed a positive relationship between weight gain in excess of Institute of Medicine guidelines and the development of milder states of glucose intolerance, although these findings were limited to Hispanic women with a BMI of ≥ 35 kg/m 2 . 40 In a clinical trial among obese Danish women, Wolff et al 28 found 20% reductions in serum insulin and leptin levels at 27 weeks of gestation, along with 8% reductions in fasting blood glucose at 36 weeks of gestation, in those women who were assigned randomly to a dietary counseling intervention to restrict weight gain to 6–7 kg in pregnancy. The authors, however, saw no reduction in the risk of incident GDM, which suggests that changes in weight during pregnancy may have a greater impact on more moderate levels of glucose intolerance, which is consistent with our findings.…”
Section: Commentmentioning
confidence: 99%